Guillaume de Machaut : Secretary, Poet, Musician - Leach, Elizabeth Eva (Book collections on Project MUSE., 2016)
At once a royal secretary, a poet and a composer, Guillaume de Machaut was one of the most protean and creative figures of the late Middle Ages. Leach makes a case that musico-literary performance occupied a special place in the courts of 14th century France.